Studi Literatur Penggunaan Metode BIM Pada Software Autodesk Revit Structure - Nanang Chandra (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2022)
Building Information Modeling (BIM) can be a useful platform for engineers in designing or modeling a building. Autodesk Revit is a BIM based architectural and structural design program. The purpose of this research is to deepen the Autodesk Revit Structure application program in terms of features, facilities provided by revit, the basis for working on the revit program, as well as detailed design steps for columns, beams and foundations. The method that will be used in this research is to collect data from several appropriate sources with the title of the study, the reference sources include books, the internet and reviews related to case studies conducted on this application. The results of this study explain the facilities needed to run the revit structure, such as buying a license and downloading the trial for students, the steps for modeling a project using autodesk revit, such as understanding the initial display of the autodex revit software, project browser,box properties, ribown menu, introducing the display initial (user interface), as well as modeling structure. The conclusion of this research is that soft drowing on autodex revit can be made in 3D, making it easier for engineers to design detailed parts and check for errors that occur. So that in certain cases if there is an error in the modeling, the engineers can correct the error without changing all parts, because with this revit application, if one part is changed, it appears that it will automatically change.